2010
DOI: 10.1080/14681811003666515
|View full text |Cite
|
Sign up to set email alerts
|

Sex education beyond school: implications for practice and research

Abstract: The negative consequences of teenage sexual behaviour are issues of concern in Britain and many other western countries. Over one-quarter of British young people are reported to become sexually active prior to the age of 16 and the rate of teenage pregnancy remains one of the highest in Western Europe. Current UK Government policy on sex education highlights the provision of skills for 'safe sex' at school to reduce teenage pregnancy rates. This paper argues that school cannot alone provide sufficient guidance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 71 publications
0
18
0
3
Order By: Relevance
“…Z realizovaných výzkumů vyplývá, že jednou z věcí, která ovlivňuje podobu sexuální výchovy v rodině, je sexuální výchova rodičů v jejich původní rodině (Byers et al, 2008;Fischer, 1987;Jaccard, Dittus, & Gordon, 2000;King & Lorusso, 1997;Miller et al, 2007;Yu, 2010). Na základě realizovaného výzkumného šetření můžeme říci, že totéž platí o rodinné sexuální kultuře.…”
Section: Závěremunclassified
“…Z realizovaných výzkumů vyplývá, že jednou z věcí, která ovlivňuje podobu sexuální výchovy v rodině, je sexuální výchova rodičů v jejich původní rodině (Byers et al, 2008;Fischer, 1987;Jaccard, Dittus, & Gordon, 2000;King & Lorusso, 1997;Miller et al, 2007;Yu, 2010). Na základě realizovaného výzkumného šetření můžeme říci, že totéž platí o rodinné sexuální kultuře.…”
Section: Závěremunclassified
“…42 sexuální výchovy (Alexander, 1984;Wellings, Wadsworth, Johnson, Field, & Macdowall, 1999;somers & surmann, 2004;Macdowall, Wellings, Mercer, nanchahal, Copas … Johnson, 2006). Důvodem může být fakt, že sex je v rámci mnoha kultur vnímán jako tabuizované téma k domácí diskusi ( Jaccard, Dittus, & Gordon, 2000;Yu, 2010), nebo neochota rodičů o té-matu mluvit. Co tedy způsobuje fakt, že děti uvádějí rodiče jako preferovaný zdroj sexuální výchovy, ale ve skutečnosti tomu tak není?…”
Section: Rodiče a Jejich Role Při Sexuální Výchově V Rodiněunclassified
“…Důvodem může být fakt, že sex je v rámci mnoha kultur vnímán jako tabuizované téma k domácí diskusi ( Jaccard, Dittus, & Gordon, 2000;Yu, 2010), nebo neochota rodičů o té-matu mluvit. Co tedy způsobuje fakt, že děti uvádějí rodiče jako preferovaný zdroj sexuální výchovy, ale ve skutečnosti tomu tak není?…”
unclassified
“…The family has a profound role to play on how young people shape their sexual values and behaviour, mainly through positive parental interaction and monitoring of children's behaviour. 57 Young people of course live at home while at school before they ever go to university or migrate to cities to work. Evidence has shown that they often receive very limited input on sex from their parents.…”
Section: Comprehensive Sex Education Programmesmentioning
confidence: 99%